Information systems for sustainable development - Hilty, Lorenz M.; Seifert, E. K.; Treibert, Renâe (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This title provides a survey on approaches to information systems supporting sustainable development in the private or public sector. It also documents and encourages the first steps of environmental information processing towards this more comprehensive goal
Includes bibliographical references and index
Keywords: Sustainable development; Information technology